Synthesis of [7]phenacene incorporating tetradecyl chains in the axis positions and its application in field-effect transistors. Issue 22 (6th May 2020) - Okamoto, Hideki; Hamao, Shino; Kozasa, Keiko; Wang, Yanan; Kubozono, Yoshihiro; Pan, Yong-He; Yen, Yu-Hsiang; Hoffmann, Germar; Tani, Fumito; Goto, Kenta
Abstract : Ditetradecyl-substituted [7]phenacene was prepared and applied in thin-film FET devices, displaying higher mobility compared to parent [7]phenacene. Abstract : Field-effect transistors (FETs) were fabricated using a new type of phenacene molecule, 3, 12-ditetradecyl[7]phenacene ((C14 H29 )2 -[7]phenacene), and solid gate dielectrics or an electric double layer (EDL) capacitor with an ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate (bmim[PF6 ])). The new molecule, (C14 H29 )2 -[7]phenacene, was efficiently synthesized via the Mallory photoreaction. Its crystal structure and electronic properties were determined, using X-ray diffraction, scanning tunneling microscopy/spectroscopy (STM and STS), absorption spectroscopy, and photoelectron yield spectroscopy, which showed a monoclinic crystal lattice (space group P 21 (no. 4)) and an energy gap of ∼3.0 eV. The STM image clearly showed the molecular structure of (C14 H29 )2 -[7]phenacene, as well as the closed molecular stacking, indicative of a strong fastener effect between alkyl chains. The X-ray diffraction pattern of thin films of (C14 H29 )2 -[7]phenacene formed on a SiO2 /Si substrate suggested that the molecule stood on the surface with an inclined angle of 30° with respect to the normal axis of the surface. The FET properties were recorded in two-terminal measurement mode, showing p-channel normally-off characteristics. The averaged values of field-effect mobility, μ, were 1.6(3) cm 2 V −1 s −1 for a (C14 H29 )2 -[7]phenacene thin-film FET with a SiO2 gate dielectric and 6(4) × 10 −1 cm 2 V −1 s −1 for a (C14 H29 )2 -[7]phenacene thin-film EDL FET with bmim[PF6 ]. Thus, higher FET performance was obtained with an FET using a thin film of (C14 H29 )2 -[7]phenacene compared to parent [7]phenacene. This study could pioneer an avenue for the realization of high-performance FETs through the addition of alkyl chains to phenacene molecules.